A principal component simulation of age-specific fertility: Impacts of family and social policy on reproductive behavior in Germany - Patrizio Vanella; Philipp Deschermeier (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This contribution proposes a simulation approach for the indirect estimation of age-specific fertility rates (ASFRs) and the total fertility rate (TFR) for Germany via time series modeling of the principal components of the ASFRs. The model accounts for cross-correlation and autocorrelation among the ASFR time series. The effects of certain measures are also quantified through the introduction of policy variables. Our approach is applicable to probabilistic sensitivity analyses investigating the potential outcome of political intervention. A slight increase in the TFR is probable until 2040. In the median scenario, the TFR will increase from 1.6 in 2016 to 1.68 in 2040 and will be between 1.46 and 1.92 with a probability of 75%. Based on this result, it is unlikely that the fertility level will fall back to its extremely low levels of the mid-1990s. Two simple alternate scenarios are used to illustrate the estimated ceteris paribus effect of changes in our policy variables on the TFR.
Keywords: C22; C49; C53; C54; E62; J11; J13; J38; 330; Fertility; Statistical Demography; Forecasting; Family Policy; Principal Component Analysis; Time Series Analysis